INTERAKSI MANTAN NARAPIDANA DI TENGAH MASYARAKAT (STUDI TENTANG MANTAN NARAPIDANA DI DESA BATU LANGKAH KECIL KECAMATAN KUOK KABUPATEN KAMPAR - Mahmudah, Raudhatul; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was conducted in the village of Batu Langkah Kecil Kuok District of Kamparregency. This study entitled ‘‘The Interaction of Former Prisoners in Society (Studies FormerPrisoners in The Village of Batu Langkah Kecil, Kuok District Kampar Regency)’’. Topicsfocus of this research are how the interaction of former prisoners in society and society’sview of ex-prisoners. The samples in this research is using purposive sampling technique.Total population of 100 people. Samples taken were 40 people has been determined ofcriteria. Using informant to research as mush as ex-convict. The author uses descriptivequantitative method. Instrument data is observation, iterviews, questionnaires,documentation. From research by the author, the author conclude that the interaction offormer prisoners in society after release it difficult to be accepted back in the community.Public perception of the ex-prisoners always thought bad and labeling criminals to exconvict.Keywords: interaction of ex-convict, in people’s views